2017
DOI: 10.15252/embr.201745130
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clocks: from stem cells to tissue homeostasis and regeneration

Abstract: The circadian clock is an evolutionarily conserved timekeeper that adapts body physiology to diurnal cycles of around 24 h by influencing a wide variety of processes such as sleep‐to‐wake transitions, feeding and fasting patterns, body temperature, and hormone regulation. The molecular clock machinery comprises a pathway that is driven by rhythmic docking of the transcription factors BMAL1 and CLOCK on clock‐controlled output genes, which results in tissue‐specific oscillatory gene expression programs. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
100
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 97 publications
2
100
0
2
Order By: Relevance
“…in fact, a circadian clock exists in every cell of the human body. The central players in these are BMal1 encoded by the gene arnTl and clock circadian regulator (clocK) by the gene clocK (19). BMScs are stem cells with the ability to differentiate in vitro into adipocytes, osteoblasts and cartilage-forming chondroblasts (20).…”
Section: Discussionmentioning
confidence: 99%
“…in fact, a circadian clock exists in every cell of the human body. The central players in these are BMal1 encoded by the gene arnTl and clock circadian regulator (clocK) by the gene clocK (19). BMScs are stem cells with the ability to differentiate in vitro into adipocytes, osteoblasts and cartilage-forming chondroblasts (20).…”
Section: Discussionmentioning
confidence: 99%
“…REV-ERB | circadian rhythms | SR9009 | ligand | specificity T he cell-autonomous circadian clock regulates a plethora of physiological processes in the human body (1)(2)(3). The importance of proper clock maintenance is highlighted by linkages between circadian desynchrony and a variety of illnesses, including sleep and metabolic disorders, cardiovascular diseases, and cancer (1,2,(4)(5)(6)(7). This has fueled recent interest in the circadian clock as a therapeutic target (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…One hypothesis states that the clock does not oscillate, or that it is non-functional in stem cells to allow them to grow faster than differentiated cells [34353637]. Our findings suggest that oscillation of clock genes may be present in certain stem cells, and in future this information could be used as biomarkers to differentiate between different stem cell types.…”
Section: Discussionmentioning
confidence: 68%
“…A functional clock is present in adult stem cells. Here, circadian oscillations have a clear impact on driving proliferation and differentiation, thus enhancing both tissue homeostasis and regeneration [35]. Many in vitro studies have shown that pluripotent cells have no obvious rhythmicity, but their differentiated counterparts – even multipotent neural precursor cells (NPCs) – have robust circadian oscillations [36].…”
Section: Discussionmentioning
confidence: 99%